2018
DOI: 10.1002/chem.201801541
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐influenced Structure–Activity Correlations in Stoichiometric and Catalytic Reactions of Lithium Monoamido‐Monohydrido‐Dialkylaluminates

Abstract: A series of heteroleptic monoamido‐monohydrido‐dialkylaluminate complexes of general formula [iBu2AlTMPHLi⋅donor] were synthesized and characterised in solution and in the solid state. Applying these complexes in catalytic hydroboration reactions with representative aldehydes and ketones reveals that all are competent, however a definite donor substituent effect is discernible. The bifunctional nature of the complexes is also probed by assessing their performance in metallation of a triazole and phenylacetylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 86 publications
(38 reference statements)
0
26
0
1
Order By: Relevance
“…Stoichiometric reactions of TMP‐containing 1 and 4 with terminal alkyne phenylacetylene (PhCCH) in C 6 D 6 , reveal deprotonation of PhCCH at room temperature, in agreement with the fact that hydroboration of PhCCH with 1 implicated deprotonation as a key step 8b. Alternatively 3 is unreactive with PhCCH, and 6 only very slowly hydroaluminates PhCCH, at room temperature.…”
mentioning
confidence: 64%
“…Stoichiometric reactions of TMP‐containing 1 and 4 with terminal alkyne phenylacetylene (PhCCH) in C 6 D 6 , reveal deprotonation of PhCCH at room temperature, in agreement with the fact that hydroboration of PhCCH with 1 implicated deprotonation as a key step 8b. Alternatively 3 is unreactive with PhCCH, and 6 only very slowly hydroaluminates PhCCH, at room temperature.…”
mentioning
confidence: 64%
“…Recently Harder and co‐workers used it as a catalyst for the hydrogenation of imines [7c] . Our own group employed various derivatives of LiAlH 4 for catalytic hydrophosphination [5a] and hydroboration [3g–i] processes. For the latter we carried out a comparative study on the performance of neutral (monometallic) and anionic (bimetallic) aluminium complexes (depicted in Scheme 3), and found that the bimetallic catalysts ([( i Bu) 2 Al(TMP)(H)Li] 2 ( 4 ), [(HMDS) 2 Al(H)(μ‐H)Li⋅(THF) 3 ] ( 5 ), [( i Bu) 3 Al(H)Li] ( 6 )) outperform their monometallic counterparts ([( i Bu) 2 Al(TMP)] ( 7 ), [(HMDS) 2 Al(H)] ( 8 ), [( i Bu) 3 Al(H)] ( 9 )) in the conversion of aldehydes, ketones, and imines.…”
Section: Emerging Alkali‐metal‐mediated Applicationsmentioning
confidence: 99%
“…[5] Although these applications are based on stoichiometric use of LiAlH 4 ,t he last decades have seen some interesting examples of LiAlH 4 (or related compounds) in catalysis. [6][7][8][9][10][11][12][13] During the development of early main group metal catalyzed imine hydrogenation, [14] we found that commercially availableL iAlH 4 can be used under relatively mild conditions in catalytic instead of stoichiometric quantities (2.5 mol %c atalyst loading, 1bar H 2 and 85 8C). [13,15] Such an on-stoichiometric route prevents the generally hazardous aqueous work-up anda voids considerable amountso fL i/Al salts as side-products.…”
Section: Introductionmentioning
confidence: 99%